Penerapan Metode Bermain Peran Untuk Meningkatkan Hasil belajar Siswa Kelas 4 SD Pada Pembelajaran Tema 4 Pada Materi IPS - Sifaniar Harya; Susilawati; Ita Rustiati Ridwan (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
In IPS, there.are a few contemplations that are firmly related to.the sociologies, like monetary viewpoints, social collaboration, history, geography. A play scene that can't be isolated from the understudies in grade school. through playing understudies can foster agreement and influence understudies to feel glad in play. This foundation was driven by perceptions at SDN Serang VII during learning in the 4th grade in October 2021, in this perception tracked down that instructors in conveying material too exhausting even caused understudies to become idle, and learning results were missing, particularly in IPS. The method.used.in this.study.is a homeroom movement research. (PTK) with plans from Kemmis and Taggart, by having 4 stages in it in each cycle, comprising of planning, execution, perception, and reflection, with a quantitative methodology. Information data in research: meetings, tests and variety. In the use of the pretending technique in the investigation of topic 4 (IPS) to further develop understudy learning results in grade 4 experienced changes in amount, the change was seen from understudy exercises, instructors and understudy learning results, in the pre-pattern of understudy action by 430 (47% of classifications less), cycle I by 560 (62% great classification), cycle II 782 (78% with great classification), then, at that point, on educator movement during pre-cycle 44% with classification (adequate), then, at that point, expanded in cycle I 88% (great) and expanded in cycle II 94% with class (great), and afterward on understudy learning results during pre-cycle 1,460 with a normal score of 58.4 with a rate (28% class less), then, at that point, in cycle I 1,915 with a normal score of 76 with a rate (44% of adequate classes) and expanded in cycle II 2,210 with a normal score of 88.4 with a rate (88% great classification), Thus the ends got in this review in the application.of the strategy for cultivating to further develop the learning results of fourth grade understudies in subject 4 learning (IPS) are announced effective, in light of the fact that there has been an increment and change in the amount of learning in the class.